1973
DOI: 10.1258/002367773780943996
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anaemia in monkeys

Abstract: 20 healthy young adult male rhesus monkeys were bled 3 times a week in an attempt to induce an anaemia and a depletion of iron stores. A mean haemoglobin of 6·1 g/IOO ml and a haematocrit of 23 % were obtained by 30 days. The iron saturation had fallen to a level of 11% and the reticulocyte response to 4·6 %. Of note was the short period required to induce these haematological changes, and the minimal impact on the animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Narasinga Rao et al [12] demonstrated the usefulness of the monkey as an animal model for iron absorption studies. Apart from phylo genetic closeness to humans, the ferrokinetics of monkeys are also similar to those of hu mans [13,14], Therefore, the monkey was chosen as an animal model to test the validity of serum ferritin and also to understand the sequential changes in iron status parameters with the development of mild iron defi ciency.…”
mentioning
confidence: 99%
“…Narasinga Rao et al [12] demonstrated the usefulness of the monkey as an animal model for iron absorption studies. Apart from phylo genetic closeness to humans, the ferrokinetics of monkeys are also similar to those of hu mans [13,14], Therefore, the monkey was chosen as an animal model to test the validity of serum ferritin and also to understand the sequential changes in iron status parameters with the development of mild iron defi ciency.…”
mentioning
confidence: 99%
“…The exper imental design, the mode of iron depletion-repletion and the initial hematological and bone marrow grading of the animals are given in table l. The control animals were subdivided into 2 groups (groups l and 2) and received an iron-depleted diet. In addition, phleboto my was carried out in group 2 animals by removing about 10% of their estimated blood volume per week for 7 weeks [6], The iron-deficient monkeys were sub divided into 4 groups (groups 3-6) and were repleted for a period of 3 months. Groups l -4 received an irondeficient diet which contained only 20-30 mg of iron/ kg.…”
Section: Materials and M Ethodsmentioning
confidence: 99%